2000
DOI: 10.1128/iai.68.8.4384-4390.2000
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of a Plasmid in Virulence of Campylobacter jejuni 81-176

Abstract: Campylobacter jejuni strain 81-176 contains two, previously undescribed plasmids, each of which is approximately 35 kb in size. Although one of the plasmids, termed pTet, carries a tetO gene, conjugative transfer of tetracycline resistance to another strain of C. jejuni could not be demonstrated. Partial sequence analysis of the second plasmid, pVir, revealed the presence of four open reading frames which encode proteins with significant sequence similarity to Helicobacter pylori proteins, including one encode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
310
4
7

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 347 publications
(339 citation statements)
references
References 63 publications
15
310
4
7
Order By: Relevance
“…has been shown to vary considerably between 44 and 91% for clinical and poultry isolates respectively in one study [75], compared with a plasmid isolation rate of 19% reported in a separate study [14]. As shown in Table II, tetracycline, kanamycin and chloramphenicol resistances are primarily plasmid-mediated.…”
Section: Genetic Mechanisms Associatedmentioning
confidence: 87%
See 1 more Smart Citation
“…has been shown to vary considerably between 44 and 91% for clinical and poultry isolates respectively in one study [75], compared with a plasmid isolation rate of 19% reported in a separate study [14]. As shown in Table II, tetracycline, kanamycin and chloramphenicol resistances are primarily plasmid-mediated.…”
Section: Genetic Mechanisms Associatedmentioning
confidence: 87%
“…Emergence of resistance to these agents however, has since made their efficacy less certain. Resistance was reported to develop among patients after treatment with fluoroquinolones [14], and was also found to coincide with the introduction of these agents in veterinary medicine [1,2,38]. However, an increasing number of Campylobacter isolates resistant to these drugs are now being cultured from both clinical and food samples in several European countries, Canada and the United States.…”
Section: Antibiotic Resistancementioning
confidence: 99%
“…As sublethally injured C. jejuni are sensitive to selective agents, selective enrichment will negatively influence the culturability [34] and the presence of a few culturable C. jejuni might be not detected. Another explanation might be the use of in vivo instead of in vitro models, although previous studies showed a correlation between the adhesion and invasion properties and IL-8 values in vitro to the infectivity in vivo [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…Instead of mediating DNA transfer between bacteria, these systems deliver DNA or protein substrates, known as effectors, to eukaryotic target cells during infection [3][4][5] . More recently, several new T4S systems have been described that are also ancestrally related to the conjugation machines, but these systems mediate the exchange of DNA with the extracellular milieu [6][7][8] . Collectively, this diversity of function in the face of a common ancestry makes the T4S machines attractive subjects for comparative studies that explore the dynamics of organelle assembly and action.…”
Section: The Year 2003 Marks the Fiftieth Anniversary Of The First Dementioning
confidence: 99%
“…1; Table 1). This recently discovered subfamily presently comprises two COMPETENCE (DNA-uptake) systems -the Campylobacter jejuni Cjp/VirB system and the Helicobacter pylori ComB system 6,7,17,18 -and one DNArelease system, an F-plasmid Tra-like system that is carried on the gonococcal genetic island (GGI) of Neisseria gonorrhoeae 8,19 . As with the conjugation machines, these systems promote genetic exchange and therefore also represent potential mechanisms for the transfer of survival traits during infection 20 .…”
Section: The T4s Familymentioning
confidence: 99%